High-temperature wettability study of mineral waste added CaO–CaF2–SiO2 and CaO–TiO2–SiO2-based electrode coating for offshore welds. (April 2020) - Khan, Waris Nawaz; Kumar, Jagdish; Chhibber, Rahul
This paper investigates the high-temperature wettability property of the mineral waste red ochre added CaO–CaF2 –SiO2 and CaO–TiO2 –SiO2 -based electrode coating mixture for offshore welding. The extreme vertices design method was applied to formulate 21 coating compositions. The pellets made from developed electrode coating compositions were exposed to a high temperature of 1250℃ on the substrate of super duplex stainless steel of 2507 grade. The molten flux has been characterized for contact angle, surface tension, adhesion energy and spreadability. The regression analysis has been used to estimate the effect of individual components and their interactions on the wettability property parameters. The developed regression models have been optimized using multiresponse optimization to achieve optimum flux composition. Structural analysis of flux mixture has been done using X-ray diffraction and Fourier transformation spectroscopy.